2021
DOI: 10.53370/001c.24293
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bio-Coagulant Aid to Treat High Turbid Water Containing Humic Acids

Abstract: In general, coagulation o coagulant; h As a result, t and coagulan the use of C Middle East, produced ag tests were ca the optimum of the jar tes reduce the p

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It signifies that a compound could possibly have alcohol content, however, the peak is so weak may be due to the absence of a homogeneous powder sample during preparation. However, studies revealed that the major functional group associated with Corchorus olitorius L. mucilage is attributed to the presence of phenolic content [16,17,20,21] .…”
Section: Ftir Analysis Of Corchuros Olitorius L (Saluyot) Mucilage Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…It signifies that a compound could possibly have alcohol content, however, the peak is so weak may be due to the absence of a homogeneous powder sample during preparation. However, studies revealed that the major functional group associated with Corchorus olitorius L. mucilage is attributed to the presence of phenolic content [16,17,20,21] .…”
Section: Ftir Analysis Of Corchuros Olitorius L (Saluyot) Mucilage Po...mentioning
confidence: 99%
“…Settling time at 90 minutes resulted in a higher reduction of turbidity, TSS, nitrogen, phosphorus, and BOD. This is attributed to the presence of high concentrations of both carbohydrates and lipids in the stems which can increase the content of organic matter in the treated water and represents a disadvantage due to the increase in turbidity in certain situations if the dose of the primary coagulant is not well adjusted [20] . When Corchorus olitorius L. was tried as a sole coagulant, removal of turbidity was poor as compared to alum [21] .…”
Section: Optimization Of Corchuros Olitorius L (C 100 )mentioning
confidence: 99%
“…In wastewater purification Al 3+ ions in alum binds and precipitates phosphate. As a coagulant, alum is very effective for precipitating colloidal particles and suspensions in wastewater (Altaher et al, 2016).…”
Section: Effect Of Coagulant Concentration On Test Pa-mentioning
confidence: 99%
“…Meanwhile, the flocculation process involves the agglomeration of particles, forming into a bigger size [ 9 , 10 , 11 ]. By applying the coagulation and flocculation treatments, concentrated heavy metals, organics, colour, chemical oxygen demand (COD) and total suspended solids are expected to be removed effectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%